2009
DOI: 10.1111/j.1750-3841.2009.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 0.1% Ammonium Hydroxide to Replace Sodium Tripolyphosphate in Fresh Meat Injection Brines

Abstract: Paired USDA Select beef strip loins (n = 10), aged 2 d, were injected with either an alkaline-based (3.6% sodium chloride, 1% Herbalox seasoning, adjusted to pH 10 with ammonium hydroxide [approximately 0.1%, FFC grade]) or a phosphate-based (3.6% sodium chloride, 1% Herbalox seasoning, 4.5% sodium tripolyphosphate) brine. Steaks were evaluated for 19 d. Overall, phosphate-injected steaks performed better than alkaline-injected steaks with respect to cook yield, water holding capacity, lipid oxidation, color s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
7
14
1
Order By: Relevance
“…They also noted that increasing pump rate to 30% resulted in slightly nonmeat texture, which was also observed by Nath and others (2006). Findings in the current study were also an improvement over the results reported by Cerruto‐Noya and others (2009). They found steaks injected with only 0.1% ammonium hydroxide were significantly less tender and juicy, and connective tissue scores were also higher than their phosphate injected counterparts.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…They also noted that increasing pump rate to 30% resulted in slightly nonmeat texture, which was also observed by Nath and others (2006). Findings in the current study were also an improvement over the results reported by Cerruto‐Noya and others (2009). They found steaks injected with only 0.1% ammonium hydroxide were significantly less tender and juicy, and connective tissue scores were also higher than their phosphate injected counterparts.…”
Section: Resultssupporting
confidence: 69%
“…They observed increasing cook loss over time except for rectus femoris beef steaks where cook loss increased from day 1 to 7 and then decreased from day 7 to 14. The cook loss reported for CON steaks was similar to those containing SP reported by Cerruto‐Noya and others (2009). However, they reported that steaks from beef loins injected with 0.1% ammonium hydroxide had almost 27% cook loss by day 14 retail display.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Fillets selected ( = 8/treatment) for thiobarbituric acid reactive substance (TBARs) content were utilized to measure lipid oxidation with a modified method of Buege and Aust (1978) as described by Cerruto-Noya et al [30]. …”
Section: Lipid Oxidationmentioning
confidence: 99%
“…We previously studied the replacement of phosphates by AH in the formulation of meat brines. When 1% AH was used, the results, in terms of quality parameters such as tenderness, juiciness, color stability, and lipid oxidation, were equivalent to those obtained from phosphate-injected steaks (2,11). These results look promising for the industry, since this would allow the meat industry to produce phosphate-free and lower-sodium-content meat products.…”
mentioning
confidence: 49%